International monetary and financial issues for the developing countries (U.N. New YorkUS, 1987)
Discusses main issues in international monetary reform such as the exchange rate system, surveillance, liquidity, role of the IMF, debt and resource transfers. Describes the floating exchange rate system and proposes a macro-economic policy framework for exchange-rate stability. Examines adjustment in developing countries and shows how several were affected by and responded to external shocks during 1978-82. Proposes unorthodox techniques in policy reform. Discusses international debt reform and SDR allocations as a result of resolving problems of excess liquidity and of meeting developing countries' reserve needs.
Includes bibliographical references